Spiral arm crossings inferred from ridges in Gaia stellar velocity distributions. Issue 3 (1st August 2018) - Quillen, Alice C; Carrillo, Ismael; Anders, Friedrich; McMillan, Paul; Hilmi, Tariq; Monari, Giacomo; Minchev, Ivan; Chiappini, Cristina; Khalatyan, Arman; Steinmetz, Matthias
ABSTRACT: The solar neighbourhood contains disc stars that have recently crossed spiral arms in the Galaxy. We propose that boundaries in local velocity distributions separate stars that have recently crossed and been more strongly perturbed by a particular arm from those that haven't. Ridges in the stellar velocity distributions constructed from the second Gaia data release trace orbits that could have touched nearby spiral arms at apocentre or pericentre. The multiple ridges and arcs seen in local velocity distributions are consistent with the presence of multiple spiral features and different pattern speeds and imply that the outer Galaxy is flocculent rather than grand design.